2018
DOI: 10.3892/mmr.2018.9702
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA MLK7‑AS1 promotes proliferation in human colorectal cancer via downregulation of p21 expression

Abstract: Current studies have highlighted long non-coding RNAs (lncRNAs) as critical regulators in various cancers, including colorectal cancer (CRC). By utilizing publicly available data from The Cancer Genome Atlas dataset, MLK7 antisense RNA 1 (MLK7-AS1) was identified as a novel lncRNA that correlated with CRC progression. The results of reverse transcription-quantitative polymerase chain reaction (RT-qPCR) revealed a significant upregulation of MLK7-AS1 in both CRC tissue samples and cell lines. In addition, a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…p21 is a crucial regulator of cell cycle progression and serves an important role in tumorigenesis and is regarded as a tumor suppressive protein. Numerous studies have reported that the downregulation of p21 is involved in a number of human cancers and is associated with cell proliferation (38,39). p21 may also act independently or with other cell cycle regulators, such as the CDK4/6 complex and p53 (13).…”
Section: Discussionmentioning
confidence: 99%
“…p21 is a crucial regulator of cell cycle progression and serves an important role in tumorigenesis and is regarded as a tumor suppressive protein. Numerous studies have reported that the downregulation of p21 is involved in a number of human cancers and is associated with cell proliferation (38,39). p21 may also act independently or with other cell cycle regulators, such as the CDK4/6 complex and p53 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data supports the hypothesis that targeting apoptosis may be a promising and protective strategy for the management of colorectal cancer. MLK7-AS1 knockdown promoted CRC cell apoptosis in vitro (28). Lupeol-induced cellular apoptosis of both colorectal cancer cell lines, which increased p53 and decreased Bcl2 protein levels (29).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the increased MLK7-AS1 expression was positively correlated to a series of clinicopathological factors in patients with CRC. 28 Li et al reported that long noncoding RNA FGD5 antisense RNA 1 (FGD5-AS1) was increased in CRC cells9. 29 However, the molecular mechanisms of lncRNAs in CRC progression have not been fully understood yet.…”
Section: Discussionmentioning
confidence: 99%